Konseling Kelompok Untuk Kenakalan Remaja - Ralasari, Tri Mega (STKIP Andi Matappa, 2019)
Juvenile delinquency is one of the activities of individuals aged between 12 / 13-20 / 21 years who tend to negative things. Ordinary behavior becomes destructive behavior or disturbing other individuals, as a manifestation of superior or inferior feelings it has in order to gain recognition from others. Juvenile delinquency often arises in a variety of situations and conditions, the range of norms prevailing in society so that these social problems cause social problems there is no strict supervision of various related parties such as family, environment, government and school. Referring to that, it is necessary to do group counseling departing on group care as a solution to the problem concerned while maintaining the privacy of individuals juvenile delinquents who have similar forum characteristics. Groups become the preferred alternative in conflict resolution because, the influence of groups in adolescents has greater power to be able to give effect to peer (group attachment).